Low-dose growth hormone inhibits 11 beta-hydroxysteroid dehydrogenase type 1 but has no effect upon fat mass in patients with simple obesity. - Tomlinson, J; Crabtree, N; Clark, P; Holder, G; Toogood, A; Shackleton, C; Stewart, P (2003)
GH has potent effects on adipocyte biology, stimulating lipolysis but also promoting preadipocyte proliferation. In addition, GH, acting through IGF-I, inhibits 11 beta-hydroxysteroid dehydrogenase type 1 (11 beta-HSD1), which converts the inactive glucocorticoid, cortisone (E), to active cortisol (F) in adipose tissue. Although F is an essential requirement for adipocyte differentiation, it also inhibits preadipocyte proliferation. We hypothesized that inhibition of 11 beta-HSD1 activity in adipose tissue by GH may alter fat tissue mass through changes in local F concentrations. We conducted a randomized, double-blind, placebo-controlled study using low-dose GH (Genotropin 0.4 mg/d) for 8 months in 24 patients with obesity. Although GH treatment significantly raised IGF-I, we were unable to demonstrate significant differences in body composition or metabolic profiles between GH- and placebo-treated groups. In addition, there was no alteration in total fat mass over time in the GH-treated group [total fat mass 41.0 +/- 3.0 vs. 41.3 +/- 3.4 kg (8 months), mean +/- SE, P = ns]. However, in comparison with baseline values, systolic blood pressure increased (119 +/- 3 vs. 130 +/- 4 mm Hg, P < 0.05 vs. baseline) and serum F/E ratio decreased (6.1 +/- 0.5 vs. 3.9 +/- 0.5, P < 0.05 vs. baseline) in the GH-treated group only. Furthermore, although the urinary tetrahydrometabolites of F/E ratio fell in the GH-treated group, it rose in the placebo group (mean ratio change, -0.13 +/- 0.05 vs. +0.09 +/- 0.09, GH vs. placebo, P = 0.07). Treatment with low-dose GH in obesity fails to alter fat mass despite a significant elevation in IGF-I and a shift in the global set point of E to F conversion consistent with inhibition of 11 beta-HSD1.